Benchmarking Public Procurement as an International Rating System for Evaluation the Effectiveness of Public Procurement System of the Countries - Shalimova, N.; Kuzmenko, H.; Шалімова, Н. С.; Кузьменко, Г. І. (My University, 2020)
The purpose of the article is to study the methodology of assessing the effectiveness of the public procurement system by World Bank, to conduct a comparative analysis of Ukraine's place among other countries in the world. Taking into account the globalization of the economy and the intensification of European integration processes, it has been proved that an important part of evaluating the effectiveness of public procurement should be a comparative analysis of the implementation procedures with the relevant systems of other countries of the world. The methodologies of the World Bank's Benchmarking Public Procurement system are investigated. A comparative analysis of the Ukraine’s place among other countries of the world, in particular among the group of countries of Europe and Central Asia, as well as with some OECD countries, which are considered as a group of high-income countries, has been conducted. Taking into account that the World Bank reports do not have a final score and a final rating, it has been justified the feasibility of comparing by the general amount of points. It is substantiated that the results of such comparative analysis will allow identifying risk areas, and relevant information can be used in developing of recommendations and proposals for improving the effectiveness of the public procurement system, especially in the context of reforming the law on public procurement and the introduction of the new system "Prozorro". As a prospects for further researches the study of second-tier indicators and the methodology of evaluating the public procurement systems by the World Bank, taking into account its relatively short setbacks compared to other ratings, have been identified.
Keywords: public procurement; public procurement system; international ratings; Benchmarking Public Procurement; efficiency; assessment; evaluation